Analisis Yuridis Jasa Pembuatan Skripsi Sebagai Tindak Pidana Akademis dan Etika Hukum - Tuulima, Moreno Ariel; Leo, Rudepel Petrus; Wilhelmus, Bhisa Vitus (Law Faculty, Nusa Cendana University, 2025)
This study examines the legal analysis of thesis-writing services as an academic crime and legal ethics violation. The background of this research is based on the widespread practice of thesis-writing services that undermine academic integrity and contradict the principles of honesty in education. Based on this background, the study formulates two main issues: (1) What is the legal position of thesis-writing services from the perspective of criminal law and copyright law in Indonesia? (2) What are the legal responsibilities of thesis-writing service providers from the aspects of criminal law and legal ethics?.. The research method used is normative juridical research with a statute approach and a conceptual approach.The results indicate that the practice of thesis-writing services violates Law Number 28 of 2014 on Copyright, Law Number 20 of 2003 on the National Education System, and can be prosecuted under articles in the Indonesian Penal Code (KUHP) related to document forgery. From the perspective of legal ethics, this practice undermines academic honesty and fosters a culture of academic dishonesty. Therefore, stricter law enforcement and increased awareness of academic integrity are necessary to prevent this practice from spreading further.